Pengaruh Promosi dan Kualitas Produk terhadap Keputusan Pembelian Produk Yosan pada Konsumen PT Mustika Manis Utama : The Influence of Promotion and Product Quality on Yosan Product Purchase Decisions on Consumers PT Mustika Manis Utama - Ika Fibriyanti; Heri Kuswara (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to examine the effect of promotion and product quality on the purchase decision of Yosan products among consumers of PT Mustika Manis Utama. This research employed a quantitative method with a sample of 68 respondents selected using purposive sampling. The data were analyzed using IBM SPSS Statistics version 29. The results indicate that promotion and product quality have a positive and significant effect on purchase decisions, both partially and simultaneously. This is evidenced by the promotion t-value of 3.796, the product quality t-value of 4.760, and the F-value of 162.002, with a significance level of 0.000 < 0.05. The R Square value of 0.833 indicates that promotion and product quality explain 83.3% of the variation in purchase decisions, while the remaining 16.7% is influenced by other variables not examined in this study.